STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI SIKAP TOLERANSI BERAGAMA PADA PESERTA DIDIK DI SD NASIONAL KOTA MAKASSAR - Ariesta Putri Dewi S; Muh. Aidil Sudarmono R; Yush Nawir; Martini; Samsuddin Kade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the strategies implemented by Islamic Religious Education (PAI) teachers in instilling the values ​​of religious tolerance and to assess their effectiveness in students at Makassar City's National Elementary School. This study used a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that PAI teachers' strategies in instilling the values ​​of religious tolerance include integrating tolerance values ​​into learning materials, providing role models, cultivating tolerance in daily life, and utilizing active learning methods such as discussions and group work. These strategies have proven effective in instilling the values ​​of religious tolerance in students, demonstrated through mutual respect, appreciating differences, and creating harmonious interactions within the school environment.